Penggunaan Celengan sebagai Sarana Edukasi Literasi Keuangan diKalangan Sekolah Dasar - Putri Winanda; Dinda Amalia; Desi Khairani Harahap; M Fikri Almi; Sofia Hanin; Zulpahmi Lubis (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to examine the use of piggy banks as a means of financial literacy education among elementary school students. Piggy piggy banks are seen as a simple but effective learning medium in instilling the habit of saving, managing money, and forming a frugal character from an early age. Through a qualitative descriptive approach, this research involves students, teachers, and parents as the main data source with interview and observation techniques. The results of the study show that the use of piggy banks not only increases children's understanding of the concept of money and economic value, but also fosters financial responsibility and awareness from an early age. Teachers play an important role in providing direction and assistance, while the role of parents is a reinforcement of the practice of saving at home. In addition, saving through piggy banks has been proven to increase motivation to learn, because children feel that they have financial goals that they want to achieve. Education through piggy banks is the first step in building a strong financial literacy foundation, so that children are used to planning their money wisely and consistently. Thus, piggy banks can be used as effective contextual learning innovations at the elementary school level.